GIANT FRONTOETHMOIDAL OSTEOMAS: A RATIONAL APPROACH TO THE SURGICAL REMOVAL AND THE IMMEDIATE RECONSTRUCTION OF THE ANTERIOR WALL OF THE FRONTAL SINUS - M.K. IKROMOV (Avicenna Tajik State Medical University, 2022)
Objective: To develop an appropriate method for removing giant frontoethmoidal osteomas and the immediate reconstruction of the anterior wall of the frontal sinus. Methods: Between 2016 and 2020, five patients (4 men and 1 woman) were admitted with an osteoma of the paranasal sinuses, of which three (2 men and 1 woman) were diagnosed with giant osteomas of the frontal and ethmoid region. The patients were aged 28 to 49 years. Routine clinical examinations were carried out, including collecting patient history and a CT scan of the paranasal sinuses. The giant osteomas were removed by minimally invasive transnasal endoscopic surgery with a combined anterior wall approach to the frontal sinus. The tumour size was reduced by excision with a surgical drill before removal to minimise the defect in the frontal sinus's anterior wall. The procedure was completed with the immediate reconstruction of the anterior wall of the frontal sinus using titanium nickelide mesh. Results: The length of hospital stay was 10 days. Wound healing occurred by primary intention, and the sutures were removed on the 8th day. Followup periods were between 1 month and 1 year. Follow-up examinations were carried out 1 week, 1, 6 and 12 months after hospital discharge. On the follow-up CT scans performed a year after the operation, the implanted titanium nickelide mesh was stable, the aeration of the frontal sinus was normal, and satisfactory cosmetic outcomes were reported. Conclusion: CT is the gold standard in determining the size of the osteoma, its spread, and the state of the walls of the paranasal sinuses. A combined surgical approach and debulking of the giant osteomas using a surgical drill with the immediate reconstruction of the anterior wall of the frontal sinus by titanium nickelide mesh produce favourable outcomes.